Body adiposity and nutritional status among indigenous children in villages of Kaxinawá tribe in Southwest Amazon rain forest, State of Acre, Brazil - Orivaldo Florêncio de Souza; Edson dos Santos Farias (Universidade Federal de Santa Catarina, 2005)
The present study aimed to investigate body adiposity and nutritional status among indigenous children from Kaxinawá Tribe by using anthropometry. The sample was composed by 93 children aged 6 to 10 years and of both sexes, living at the villages Kaxinawá do Caucho e Paroá, in the state of Acre, Brazil. Body adiposity was estimated by skinfold thickness at triceps and subscapular sites and by the sum of these two skinfolds. Nutritional status was identified by the indicators weight-for age (w/a), stature-for-age (s/a) and weight-for-stature (w/s) using z-score cut-off points suggested by the World Health Organization. For comparison between sexes, the Student's t-test was used. Low body fat prevalence was observed in 83.7% of boys and 62% of girls. There were significant differences between sexes at 8 and 10 years of age for the triceps skinfolds and the sum of skinfolds. For the subscapular skinfold, the difference was observed only at 8 years of age. Chronic malnutrition was detected in both sexes and the prevalence depended upon the applied criteria. The prevalence was 76.3% for s/a and 47.3% for w/a. Acute malnutrition was present among 12.9% of children when using w/s. Boys tended to have higher prevalence for chronic malnutrition (s/a and w/a), while the girls for acute malnutrition (w/s). It was concluded that there is a high prevalence of malnutrition and low body adiposity among indigenous Kaxinawá children in the state of Acre, Brazil. RESUMO O presente estudo foi realizado com o objetivo de investigar a adiposidade corporal e o estado nutricional de crianças indígenas da Tribo Kaxinawá, através do método antropométrico. A amostra constitui-se de 93 crianças, de ambos os sexos, na faixa etária de 06 a 10 anos de idade das aldeias indígenas Kaxinawá do Caucho e Paroá, no estado do Acre. Na adiposidade corporal, verificou-se as dobras cutâneas tricipital, subescapular e somatório de dobras cutâneas (tríceps mais subescapular). E, o estado nutricional foi observado através dos indicadores peso para idade (P/I), estatura para idade (E/I) e peso para estatura (P/E), utilizando-se os pontos de corte do escores Z conforme sugerido pela Organização Mundial da Saúde. Para a comparação entre os sexos realizouse por meio do teste "t" de student. No nível de adiposidade corporal foi observado prevalência de baixo nível de gordura no sexo masculino (83,7%) e feminino (62%). Houve diferenças entre os sexos na adiposidade corporal aos 8 e 10 anos na dobra cutânea tricipital e somatório de dobras cutâneas e somente aos 8 anos na dobra cutânea subescapular. Em relação ao estado nutricional, observou-se desnutrição pregressa e crônica, em ambos os sexos, da E/I de 76,3%, seguida de 47,3% para o P/I; e, desnutrição aguda de 14% para o P/E. Os meninos mostraram nos indicadores E/I e no P/I maior desnutrição crônica, enquanto as meninas apresentaram maior desnutrição aguda no indicador P/E. Conclui-se que existe elevado contingente percentual de desnutrição e baixa adiposidade corporal nas crianças indígenas Kaxinawa do estado do Acre, Brasil.